Electroanalysis with Carbon Paste Electrodes. - Svancara, Ivan (Analytical chemistry series., 2012)
Because of their simple preparation and low expense, carbon pastes and carbon paste electrodes are widely used in a myriad of instrumental measurements. With an emphasis on practical applications, Electroanalysis with Carbon Paste Electrodes provides a comprehensive overview of carbon paste electrodes. The text offers a comprehensive and unprecedentedly wide insight into the realm of the carbon paste material, culminating with a systematic presentation of all the methods and procedures applicable to the determination of a myriad of inorganic and organic substances when employing the individual.